Point Blank : An FBI Thriller - Coulter, Catherine (New York A Jove books, 2007)
Barely surviving a motel bombing while trying to rescue a kidnapped entertainer, FBI agents Dillon Savich and Dane Carver find themselves working against an unstable villain with designs on their families and fellow agents.
Keywords: Married people -- Kidnapping